Estudo sobre a lírica da lembrança em três fragmentos de Safo de Lesbos - Silva, Odi Alexander Rocha da (2012)
This work analyses some questions concerning to as a signal of the individual s first steps towards to the search of his inner life in three fragments of Sappho of Lesbos. Our objective é to approach the remembrance as a signal of the individual at the 7th Century bC., was in his first steps to write about his inner life. The present work is a discussion about remembrance in three fragments of Sappho of Lesbos. In this discussion, the objective, the main objective is think about the way of approaching the question of remembering in the poetry of this authoress. We discuss the meaning of remembrance in the poetic context which has some resources like intertextuality and a new reading about the elements of tradition. Discuss about the question of remembrance is important because the lyric poetry of Sappho of Lesbos was one of the first moments in which the elements of inner life were considered as capable of being expressed in poetic production.